2022
DOI: 10.1021/acsami.2c04786
|View full text |Cite
|
Sign up to set email alerts
|

General Carbon-Supporting Strategy to Boost the Oxygen Reduction Activity of Zeolitic-Imidazolate-Framework-Derived Fe/N/Carbon Catalysts in Proton Exchange Membrane Fuel Cells

Abstract: The oxygen reduction reaction (ORR) activity of the Fe/N/Carbon catalysts derived from the pyrolysis of zeolitic-imidazolate-framework-8 (ZIF-8) has been still lower than that of commercial Pt-based catalysts utilized in the proton exchange membrane fuel cells (PEMFCs) due to low density of accessible active sites. In this study, an efficient carbon-supporting strategy is developed to enhance the ORR efficiency of the ZIF-derived Fe/N/Carbon catalysts by increasing the accessible active site density. The enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Zhang et al again highlight that ZIF-8-derived pyrolyzed catalysts with graphenelike carbon structures exhibit remarkable ORR electrocatalytic performances in alkaline environments, while their performances in acidic electrolytes are seldom reported [81]. The authors proposed that this disparity could be attributed to the pyrolysis process, where cracked or deformed ZIF-8 units tend to reassemble and encapsulate a significant number of active sites, resulting in fewer exposed active sites.…”
Section: Synthesis Trends and Characteristics Of N-g/zif-8-based/deri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al again highlight that ZIF-8-derived pyrolyzed catalysts with graphenelike carbon structures exhibit remarkable ORR electrocatalytic performances in alkaline environments, while their performances in acidic electrolytes are seldom reported [81]. The authors proposed that this disparity could be attributed to the pyrolysis process, where cracked or deformed ZIF-8 units tend to reassemble and encapsulate a significant number of active sites, resulting in fewer exposed active sites.…”
Section: Synthesis Trends and Characteristics Of N-g/zif-8-based/deri...mentioning
confidence: 99%
“…A number of these studies have explored various synthesis methods, characteristics, and electrochemical performances of N-G/ZIF-8-based/derived materials. Most of these investigations rely on experiments and compare the electrocatalytic performances of these materials with their precursors and standard catalysts, like Pt/C and RuO 2 [36][37][38][39][77][78][79][80][81][82]. The reported studies consistently demonstrated significantly enhanced electrocatalytic performances of N-G/ZIF-8-based/derived materials.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their diversified and tunable nanostructures, porous MOFs have been regarded as emerging precursors for the facile syntheses of single metal sites or metal compounds (such as oxides, phosphides, sulfides, selenides and others), as well as their composites for electrochemical catalysis. 178–181 On the other hand, compared with other types of MOF derivatives, multifunctional CNMs are structurally endowed with high hydrophobicity due to low polarity caused by the high graphitization degree, which greatly hinders the mass transfer and conduction process of electrocatalytic materials in a liquid. This is a common problem for MOF-derived CNMs, and is also the most urgent problem to be solved at present.…”
Section: Applicationsmentioning
confidence: 99%
“…Unfortunately, direct pyrolysis for ZIFs usually undergoes an inevitable self-aggregation, and severe morphological contraction and structural collapse, which is not conductive to boosting the catalytic performance . On this basis, an effective approach to addressing the above issues is the hybridization of ZIF derivatives and N-doped carbon substrates . Recently, one-dimensional (1D) carbons (nanotubes, nanofibers, nanorods, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…22 On this basis, an effective approach to addressing the above issues is the hybridization of ZIF derivatives and N-doped carbon substrates. 23 Recently, one-dimensional (1D) carbons (nanotubes, nanofibers, nanorods, etc.) derived from conductive polymers as templates are highly desired because of several advantages including large specific surface areas, facile generation of a conductive network, and fast mass transfer.…”
Section: Introductionmentioning
confidence: 99%